2003
DOI: 10.1046/j.1420-9101.2003.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Foundress re-emergence and fig permeability in fig tree–wasp mutualisms

Abstract: Some female pollinating fig wasps (foundresses) re‐emerge from figs after oviposition/pollination. We investigated why this occurs in the mutualism between the gynodioecious Ficus montana and Liporrhopalum tentacularis. Re‐emergence increased with foundress density in figs and some foundresses oviposited in two male figs, indicating that they re‐emerge because of oviposition site limitation. Re‐emergence was independent of fig diameter, indicating that permeability is not because of fig age at entry. Rather, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
47
0
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 44 publications
2
47
0
1
Order By: Relevance
“…As fundadoras penetram no sicônio através do ostíolo, polinizam as flores femininas e depositam ovos nos ovários de algumas delas. Na seqüência, com algumas exceções (WARE & COMPTON, 1992;GIBERNAU et al, 1996;CHEN et al, 2001;MOORE et al, 2003), as fêmeas morrem no interior do sicônio e seus corpos permanecem no lúmen. Durante as semanas seguintes, frutos (aquênios) se desenvolvem nas flores polinizadas e larvas de vespas polinizadoras crescem em flores nas quais ovos foram depositados, formando uma galha.…”
unclassified
“…As fundadoras penetram no sicônio através do ostíolo, polinizam as flores femininas e depositam ovos nos ovários de algumas delas. Na seqüência, com algumas exceções (WARE & COMPTON, 1992;GIBERNAU et al, 1996;CHEN et al, 2001;MOORE et al, 2003), as fêmeas morrem no interior do sicônio e seus corpos permanecem no lúmen. Durante as semanas seguintes, frutos (aquênios) se desenvolvem nas flores polinizadas e larvas de vespas polinizadoras crescem em flores nas quais ovos foram depositados, formando uma galha.…”
unclassified
“…Of the wasps studied here, Moore et al (2003) concluded from data published by Ware & Compton (1992) that the females of one species, Allotriozoon heterandromorphum, disperse from their figs. In another study where the focus was on sex ratio (Kjellberg et al 2005), we found no evidence for females leaving figs and we believe that the foundresses were overlooked in the Ware & Compton (1992) study cited by Moore et al (2003). When not all females contribute to the brood, or do so in unequal proportions, the optimal sex ratio is more female biased than with equal contributions (Frank 1985;Moore et al 2005).…”
mentioning
confidence: 81%
“…In light of their highly femalebiased sex ratios (Herre et al 1997), it is thus surprising that brother-brother fighting and male dispersal may have evolved as many as six times in pollinating fig wasps (Michaloud, 1988;Greeff et al 2003). In this study, our aim was to determine why the kin competition-kin structure problem has been resolved differently Moore et al 2003 for examples where females have evolved a mechanism to spread their eggs over several figs). Each egg is laid in an individual flower, each forming a distinct gall inside the inflorescence.…”
mentioning
confidence: 99%
See 2 more Smart Citations